Thoughts on and practical exploration of the integrated medicine talent development model under the trend of medical innovation in the Guangdong-Hong Kong-Macau Greater Bay Area - Song LIU; Lin XIE; Langjing SHEN; Mengdan XU; Xiong LI (KeAi Communications Co., Ltd., 2021)
[Abstract]: Talents are the first resources that drive societal progress and scientific advances. A great amount of outstanding medical talent is required for development with the times, societal progress, and assurance and improvement of national health levels. The national development strategy for the Guangdong-Hong Kong-Macau Greater Bay Area fully utilizes the strengths in medical resources and pilot testing of Macau, Hong Kong, and Guangdong to promote the upgrading of the medical industry. Guangdong Pharmaceutical University is located in the Guangdong-Hong Kong-Macau Greater Bay Area and focuses on drugs, medical integration, and its mission is to nurture outstanding medical talents. Dr. Guo, the dean of the university, proposed the idea of "integrated pharmacy" based on the theoretical foundation of "integrative medicine" by an academician, Dr. Daiming Fan. In 2016, Guangdong Pharmaceutical University was the first to open a School of Integrated Pharmacy and Integrated Pharmacy Research Institute in China, established the integrated pharmacy profession, and obtained a series of achievements. In this paper, we analyzed the strengths of the Guangdong-Hong Kong-Macau Greater Bay Area and combined it with the integrated pharmacy talent development experience of Guangdong Pharmaceutical University to propose a new "talents of integrative medicine and pharmacy" development concept and actively explored the "talents of integrative medicine and pharmacy" innovative development model. This will contribute to healthcare industry development in China and the Guangdong-Hong Kong-Macau Greater Bay Area.